1990
DOI: 10.1002/bmc.1130040304
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate/hydrogen peroxide chemiluminescence reaction. A 19F NMR probe of the reaction mechanism

Abstract: The mechanism of the oxalate/hydrogen peroxide chemiluminescence reaction has been examined by magnetic resonance techniques. Investigation of the reactive intermediates involved in chemiluminescence was carried out with bis(2,6-difluorophenyl)oxalate (DFPO) using 19F NMR to probe its reactions with aqueous hydrogen peroxide. Formation and reactions of the intermediate hydroperoxy oxalate ester B along with the formation of the half ester product C and difluorophenol D were monitored by 19F NMR. When the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…More direct experimental evidence was obtained by the study of the chemiluminescent properties of peracid intermediates involved in the peroxyoxalate sequence (21)(22)(23)(24)(25). However, the exact nature of the reactive intermediate involved and the mechanism of its interaction with the activator still remains to be clarified.…”
Section: Introductionmentioning
confidence: 96%
“…More direct experimental evidence was obtained by the study of the chemiluminescent properties of peracid intermediates involved in the peroxyoxalate sequence (21)(22)(23)(24)(25). However, the exact nature of the reactive intermediate involved and the mechanism of its interaction with the activator still remains to be clarified.…”
Section: Introductionmentioning
confidence: 96%
“…The reaction kinetics was studied using both, light emission intensity and absorption by produced phenol as parameters, and it was possible to attribute the faster rate constant of the rise in emission intensity ( In order to obtain a more precise insight into the reaction mechanism of the peroxyoxalate system, two research groups independently attempted the synthesis and study of peracid intermediates in the reaction sequence. Chokshi and coworkers 48 performed a 19 F NMR study on the reaction of bis(2,6-difluorophenyl)oxalate with hydrogen peroxide and concluded that the peracid derivative 11, should be an essential reactive intermediate in this transformation. Hohman and coworkers 49 , from the same research group, achieved the synthesis of silylprotected oxalic peracids 13 and 14 and studied their chemiluminescence properties, concluding that these compounds are involved in the reaction sequence leading to light emission.…”
mentioning
confidence: 99%
“…Givens et al 8 suggested that the hydroperoxy oxalate ester was the likely reactive intermediate based on an investigation with bis(2,6-difluorophenyl)oxalate (DFPO) using 19F-NMR.…”
mentioning
confidence: 99%